Ease and comfort of pre‐oxygenation with high‐flow nasal oxygen cannulae vs. facemask: a randomised controlled trial. (15th September 2022) - Merry, A. F.; van Waart, H.; Allen, S. J.; Baker, P. A.; Cumin, D.; Frampton, C. M. A.; Gargiulo, D. A.; Hannam, J. A.; Keogh, G. F.; Moore, M. R.; Payton, M.; Mitchell, S. J.
Summary: The Difficult Airway Society recommends that all patients should be pre‐oxygenated before the induction of general anaesthesia, but this may not always be easy or comfortable and anaesthesia may often be induced without full pre‐oxygenation. We tested the hypothesis that high‐flow nasal oxygen cannulae would be easier and more comfortable than facemasks for pre‐oxygenation. We randomly allocated 199 patients undergoing elective surgery aged ≥ 10 years to pre‐oxygenation using either high‐flow nasal oxygen or facemask. Ease and comfort were assessed by anaesthetists and patients on 10‐cm visual analogue scale and six‐point smiley face scale, respectively. Secondary endpoints included end‐tidal oxygen fraction after securing a definitive airway and time to secure an airway. A mean difference (95%CI) between groups in ratings of ‐0.76 (‐1.25 to ‐0.27) cm for ease of use (p = 0.003) and ‐0.45 (‐0.75 to ‐0.13) points for comfort (p = 0.006), both favoured high‐flow nasal oxygen. A mean difference (95%CI) between groups in end‐tidal oxygen fraction of 3.89% (2.41–5.37%) after securing a definitive airway also favoured high‐flow nasal oxygen (p < 0.001). There was no significant difference between groups in the number of patients with hypoxaemia (Sp O2 < 90%) or severe hypoxaemia (Sp O2 < 85%) lasting ≥ 1 min or ≥ 2 min; in the proportion of patients with an end‐tidal oxygen fraction < 87% in the first 5 min after tracheal intubation (52.2% vs. 58.9% in facemask and high‐flow nasal oxygen groups, respectively; p = 0.31); or in time taken to secure an airway (11.6 vs. 12.2 min in facemask and high‐flow nasal oxygen groups, respectively; p = 0.65). In conclusion, we found pre‐oxygenation with high‐flow nasal oxygen to be easier for anaesthetists and more comfortable for patients than pre‐oxygenation with a facemask, with no clinically relevant differences in end‐tidal oxygen fraction after securing a definitive airway or time to secure an airway. The differences in ease and comfort were modest.